Significant clinical impact of recurrent BRCA1 and BRCA2 mutations in Mexico. Issue 3 (18th September 2014) - Villarreal‐Garza, Cynthia; Alvarez‐Gómez, Rosa María; Pérez‐Plasencia, Carlos; Herrera, Luis A.; Herzog, Josef; Castillo, Danielle; Mohar, Alejandro; Castro, Clementina; Gallardo, Lenny N.; Gallardo, Dolores; Santibáñez, Miguel; Blazer, Kathleen R.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Frequent recurrent mutations in the breast and ovarian cancer susceptibility (BRCA) genes BRCA1 and BRCA2 among Hispanics, including a large rearrangement Mexican founder mutation (BRCA1 exon 9‐12 deletion [ex9‐12del]), suggest that an ancestry‐informed BRCA‐testing strategy could reduce disparities and promote cancer prevention by enabling economic screening for hereditary breast and ovarian cancer in Mexico. METHODS In a multistage approach, 188 patients with cancer who were unselected for family cancer history (92 with ovarian cancer and 96 with breast cancer) were screened for BRCA mutations using a Hispanic mutation panel (HISPANEL) of 115 recurrent mutations in a multiplex assay (114 were screened on a mass spectroscopy platform, and a polymerase chain reaction assay was used to screen for the BRCA1 ex9‐12del mutation). This was followed by sequencing of all BRCA exons and adjacent intronic regions and a BRCA1 multiplex ligation‐dependent probe amplification assay (MLPA) for HISPANEL‐negative patients. BRCA mutation prevalence was calculated and correlated with histology and tumor receptor status, and HISPANEL sensitivity was estimated. RESULTS BRCA mutations were detected in 26 of 92 patients (28%) with ovarian cancer, in 14 of 96 patients (15%) with breast cancer overall, and in 9 of 33 patients (27%) who had tumors that were negative for estrogen receptor, progesterone receptor, and human epithelial growth factor 2 (triple‐negative breast cancer). Most patients with breast cancer were diagnosed with locally advanced disease. The Mexican founder mutation (BRCA1 ex9‐12del) accounted for 35% of BRCA‐associated ovarian cancers and 29% of BRCA‐associated breast cancers. At 2% of the sequencing and MLPA cost, HISPANEL detected 68% of all BRCA mutations. CONCLUSIONS In this study, a remarkably high prevalence of BRCA mutations was observed among patients with ovarian cancer and breast cancer who were not selected for family history, and the BRCA1 ex9‐12del mutation explained 33% of the total. The remarkable frequency of BRCA1 ex9‐12del in Mexico City supports a nearby origin of this Mexican founder mutation and may constitute a regional public health problem. The HISPANEL mutation panel presents a translational opportunity for cost‐effective genetic testing to enable breast and ovarian cancer prevention. Cancer 2015;121:372–378. © 2014 American Cancer Society.